2003
DOI: 10.1590/s0100-06832003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Sorção de fósforo em função do teor inicial e de sistemas de manejo de solos

Abstract: RESUMOA relação entre o P sorvido/P solução do solo pode ser influenciada pelo teor de P previamente sorvido e pelos sistemas de manejo. Este trabalho teve o objetivo de avaliar as modificações na capacidade de sorção máxima (P max ) e na constante relacionada com a energia de ligação de P com os colóides (k) da isoterma de Langmuir, provocadas (a) pela inclusão do teor de P previamente sorvido (P pre ) e (b) por sistemas de manejo de solos. Coletaram-se, em maio de 1997, amostras de solo (Latossolo Vermelho d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
1
9
0
12
Order By: Relevance
“…The highest accumulation of labile inorganic P of all three studied areas was found in vineyard 2, which reinforces the tendency to P transfer in this soil. Similar results were found by Rheinheimer et al (2003), who reported P accumulation in labile fractions in soil with phosphate fertilizer. Moreover, the greatest P accumulation was found in vineyard 2 in the organic P fractions extracted by 0.5 mol L -1 NaOH and the inorganic P extracted by 1 mol L -1 HCL.…”
Section: Phosphorus Fractionssupporting
confidence: 90%
“…The highest accumulation of labile inorganic P of all three studied areas was found in vineyard 2, which reinforces the tendency to P transfer in this soil. Similar results were found by Rheinheimer et al (2003), who reported P accumulation in labile fractions in soil with phosphate fertilizer. Moreover, the greatest P accumulation was found in vineyard 2 in the organic P fractions extracted by 0.5 mol L -1 NaOH and the inorganic P extracted by 1 mol L -1 HCL.…”
Section: Phosphorus Fractionssupporting
confidence: 90%
“…The MPAC values obtained in the 0-2.5 cm layer were similar to those reported by Berwanger et al (2008), also in a Hapludult soil with a history of pig slurry application in a no-till system. These MPAC values are justified by this soil type, which has a low quantity of phosphate adsorption sites (Rheinheimer et al, 2003) due to the low clay contents (Table 1), and the presence of 1:1 type clay minerals (Embrapa, 2004;Uberti 2005) and negligible quantities of oxides (Gatiboni et al, 2008;Ceretta et al, 2010a).…”
Section: Resultsmentioning
confidence: 90%
“…Esses valores estão próximos dos encontrados por Rheinheimer et al (2003b) em Argissolo semelhante ao deste estudo e sob sistema plantio direto, condizendo com a baixa quantidade de sítios de adsorção de fosfato decorrentes do baixo teor de argila e da presença de argilominerais 2:1. As adições prévias de fosfatos e a presença de grande conteúdo de matéria orgânica na camada superficial do solo são as responsáveis pelos menores valores de CMPA, comparativamente ao solo da camada mais profunda, pois paulatinamente saturam os sítios de maior avidez por fosfatos (Parfitt, 1978;Sibanda & Yong, 1986;Barrow, 1989;Almeida et al, 2003).…”
Section: Resultsunclassified